2020
DOI: 10.1101/2020.04.03.20052571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distress of Iranian adults during the Covid-19 pandemic – More distressed than the Chinese and with different predictors

Abstract: Early papers on the mental health of the public during the Covid-19 pandemic surveyed participants from China. Outside of China, Iran has emerged as one of the most affected countries with a high death count and rate. The paper presents the first empirical evidence from Iranian adults during the Covid-19 pandemic on their level of distress and its predictors. On March 25-28, 2020, a dire time for Covid-19 in Iran, we surveyed 1058 adults from all 30 provinces in Iran using the Covid-19 Peritraumatic Distress I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Taken together, the results suggest distinct patterns of the predictors of the mental health conditions of healthcare staff in Iran and China during the COVID-19 crisis. Such distinct patterns of predictors among healthcare staff across countries resonant with an earlier study of the mental health of the public in Iran (Jahanshahi et al, 2020). Jahanshahi et al (2020) suggest the predictors differed because "different countries vary in their medical systems, the availability of personal protective equipment (PPE), cultures, labor and employment conditions, the policies of lockdown, the ease of working from home and maintaining a living in a pandemic, and the information in both mainstream and social media".…”
Section: The Risk Factors (Predictors) Vary Across Settingsmentioning
confidence: 78%
See 1 more Smart Citation
“…Taken together, the results suggest distinct patterns of the predictors of the mental health conditions of healthcare staff in Iran and China during the COVID-19 crisis. Such distinct patterns of predictors among healthcare staff across countries resonant with an earlier study of the mental health of the public in Iran (Jahanshahi et al, 2020). Jahanshahi et al (2020) suggest the predictors differed because "different countries vary in their medical systems, the availability of personal protective equipment (PPE), cultures, labor and employment conditions, the policies of lockdown, the ease of working from home and maintaining a living in a pandemic, and the information in both mainstream and social media".…”
Section: The Risk Factors (Predictors) Vary Across Settingsmentioning
confidence: 78%
“…Such distinct patterns of predictors among healthcare staff across countries resonant with an earlier study of the mental health of the public in Iran (Jahanshahi et al, 2020). Jahanshahi et al (2020) suggest the predictors differed because "different countries vary in their medical systems, the availability of personal protective equipment (PPE), cultures, labor and employment conditions, the policies of lockdown, the ease of working from home and maintaining a living in a pandemic, and the information in both mainstream and social media". Our results, hence, corroborate their suggestions, and we suggest future research to identify useful predictors of mental health in individual countries during the COVID-19 pandemic for not only the public but also healthcare staff.…”
Section: The Risk Factors (Predictors) Vary Across Settingsmentioning
confidence: 78%
“…The mean CPDI of sampled adults in Brazil is also significantly higher than the mean CPDI of 34.54 (14.92) of adults in Iran on February 28-30, 2020 (t=4.09; p<0.0001; 95% CI: 1.61 to 4.59). 7 Based on the cut-off values of distress in CPDI, 52.0% of sampled adults in Brazil experienced mild or moderate distress, and 18.8% experienced severe distress, compared to 47.0% and 14.1% in Iran and 29.3% and 5.1% in China respectively.…”
Section: Descriptive Findingsmentioning
confidence: 98%
“…9 Similarly, 14.1% of the Iranian public (n=1058) suffered severe stress and 47%, moderate stress. 10 Among Indians, a small unstructured general public survey (n = 662) reported that the respondents were preoccupied with the thoughts of COVID-19 (80%) and had sleep difficulties (12.5%), paranoia about acquiring COVID-19 (37.8%), and stress (36.4%). Four of five Indians perceived mental healthcare needs.…”
mentioning
confidence: 99%